COK‐16: A Cation‐Exchanging Metal–Organic Framework Hybrid. Issue 5 (3rd April 2013) - Bajpe, Sneha R.; Breynaert, Eric; Martin‐Calvo, Ana; Mustafa, Danilo; Calero, Sofia; Kirschhock, Christine E. A.; Martens, Johan A.
<x xml:space="preserve">Abstract</x> X‐ray spectroscopy: Substoichiometric encapsulation of polyoxometalate ions into a metal–organic framework results in a fully functional cation exchanger with accessible porosity. Cu2+ cations compensating the charge of [PW12O40]3− in the as‐synthesized material can be exchanged with cations such as Na+ and Eu3+. When exchanged with Eu3+, the material appears bright red under UV irradiation (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>